Complexities and Challenges of Compulsory Military Service for Generation Z: A Legal Review of Law No. 23 of 2019 on National Defense Resource Management - Purwantono, Rivan Achmad (Eduvest - Journal of Universal Studies, 2025)
The complexity and challenges of military conscription for Generation Z in Indonesia are crucial topics in national defense discussions. This article analyzes the implementation of Law Number 23 of 2019 on National Resource Management for State Defense in enhancing Generation Z’s national defense awareness. According to Litbang Kompas data, 57.6% of Generation Z are uninterested in joining the Indonesian National Armed Forces (TNI). Factors such as generational differences, psychosocial challenges, and misalignment with career aspirations pose significant obstacles to implementing military conscription. Additionally, the multi-actor dynamics and complexities of defense policy coordination further complicate human resource management in the national defense system. This article recommends a more flexible approach to conscription, including a voluntary system, incentives for participants, and the integration of technology in training programs. Thus, the national defense program can be more adaptive and inclusive for Generation Z. This study highlights the importance of balancing national defense obligations with individual rights and strengthening technology-based defense strategies to address modern threats.